Design of novel dopamine D2 and serotonin 5-HT2A receptors dual antagonists toward schizophrenia: An integrated study with QSAR, molecular docking, virtual screening and molecular dynamics simulations. Issue 3 (11th February 2020) - Zhang, Cuihua; Li, Qunlin; Meng, Lingwei; Ren, Yujie
Abstract: The extrapyramidal side effects of schizophrenia treatment can be significantly reduced by simultaneously targeting dopamine D2 and serotonin 5-HT2A receptors. In this study, three-dimensional quantitative structure–activity relationship (3D-QSAR) models of D2 receptor (CoMFA-1, q 2 = 0.767, r 2 = 0.969; CoMSIA-1, q 2 = 0.717, r 2 = 0.978) and 5-HT2A receptor antagonists (CoMFA-2, q 2 = 0.703, r 2 = 0.946; CoMSIA-2, q 2 = 0.675, r 2 = 0.916) were successfully constructed using 35 tetrahydropyridopyrimidinone derivatives. Topomer CoMFA and HQSAR models were then constructed to further validate and supplement above models. Results showed that all models had good predictive power and stability. Contour map analysis revealed that the electrostatic and hydrophobic fields played vital roles in the bioactivity of dual antagonists. Molecular docking and molecular dynamic studies also suggested that the hydrogen bonding, electrostatic and hydrophobic interactions played key roles in the formation of stable binding sites. Meanwhile, several key residues like ASP114, TRP100, PHE389 of dopamine D2 receptor and ASP134, PHE328, TRP324 of serotonin 5-HT2A receptor were identified. Based on above findings, seven compounds were obtained through bioisostere replacement and ten compounds were designed by contour map analysis, in which the predicted activity of compounds S6 and DS2 were equivalent to that of the template compound 15 . 3D-QSAR and ADMET predictions indicated that all newly designed compounds had great biological activity and physicochemical properties. Moreover, based on the best pharmacophore model, four compounds (Z1, Z2, Z3 and Z4 ) with new backbones were obtained by virtual screening. Overall, this study could provide theoretical guidance for the structural optimization, design and synthesis of novel dopamine D2 and serotonin 5-HT2A receptors dual antagonists. Abbreviations: 3D-QSAR Three-dimensional quantitative structure–activity relationship 5-HT2A R Serotonin 5-hydroxytryptamine 5-HT2A receptor 5-HT2C R Serotonin 5-hydroxytryptamine 5-HT2C receptor receptor CADD Computer-aided drug design CoMFA Comparative molecular field analysis CoMSIA Comparative molecular similarity index analysis D2 R Dopamine D(2) receptor GPCR G-protein coupled receptor PLS Partial least squares regression HQSAR Hologram quantitative structure–activity relationship. Communicated by Ramaswamy H. Sarma